The antero-posterior location of the mental foramen in subjects with different skeletal pattern / Juliana Khairi - Juliana , Khairi (2017)
Background: The mental foramen is an important landmark. Previous studies in Malays and Chinese indicated that its most common location is in line with the longitudinal axis of the second premolar. However, these studies did not differentiate between gender and the effect of different (prognathic, retrognathic, or normal) skeletal pattern. Patients and Methods: In this study, the antero-posterior locations of the mental foramina in relation to the dentition of 64 patients with different skeletal patterns were determined. These subjects must have a dentopantomograph with the mental foramina clearly seen on both sides of the mandible, and a lateral cephalic radiograph that enables the determination of their skeletal pattern. Results: Radiographs of 27 Malay and 37 Chinese patients were reviewed. More than seventy percent (70.3%) of subjects were female, with the remaining being male. More than half of them have a Class I skeletal pattern (51.6%), followed by Class III (28.1%) and Class II (20.3%). The mental foramen can be found anywhere from anterior to the first premolar to being in line with the first molar. The most common antero-posterior location of mental foramen was in line with the longitudinal axis of the second premolar. This finding remains constant irrespective of the gender, site and skeletal pattern of the patients. The second most common location for the mental foramen was between the first and second premolars. Conclusion: The gender, site and skeletal pattern of patients did not influence the antero-posterior location of the mental foramen in relation to the dentition.